2008 IEEE International Conference on Information Reuse and Integration 2008
DOI: 10.1109/iri.2008.4583027
|View full text |Cite
|
Sign up to set email alerts
|

Biological question answering with syntactic and semantic feature matching and an improved mean reciprocal ranking measurement

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Clustering and representation techniques assist with adequately exploring data collection and identifying clusters of similar information that share similar properties [15]. For example, to cluster text, the following algorithms have been used: Support Vector Machine (SVM) [16], k-means [17], Principal Component Analysis (PCA) [18], and Kohonen Self-Organizing Map (SOM) [19]. A full review of different clustering algorithms can be found in [20].…”
Section: Data Representation and Clusteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Clustering and representation techniques assist with adequately exploring data collection and identifying clusters of similar information that share similar properties [15]. For example, to cluster text, the following algorithms have been used: Support Vector Machine (SVM) [16], k-means [17], Principal Component Analysis (PCA) [18], and Kohonen Self-Organizing Map (SOM) [19]. A full review of different clustering algorithms can be found in [20].…”
Section: Data Representation and Clusteringmentioning
confidence: 99%
“…A full review of different clustering algorithms can be found in [20]. As shown in the work of [19], the unsupervised ML algorithm SOM [21,22] has proven to have excellent performance when clustering text data and reducing its dimensionality. Additionally, as presented in the work of [23].…”
Section: Data Representation and Clusteringmentioning
confidence: 99%
“…Semantic enrichment for biomedical text is becoming significant because of the huge corpus of biomedical vocabulary. The use of dictionaries [71,72], has been found in highly cited literature work such as [35,64,139]. Application of ontologies [51, 76,77] has been cited in the literature work such as [72,75,78,158] employing multiple ontologies for creating a better knowledge corpus.…”
Section: Regular Expression Matching For Question Answer Pair Extract...mentioning
confidence: 99%
“…In [47], authors describe a QA system for computing answers to questions related to protein-protein interactions. They used a pipeline composed of named-entity recognition, semantic role labeling, question classification and query expansion.…”
Section: Other Research Workmentioning
confidence: 99%